Hierarchical construction of an ultrathin layered double hydroxide nanoarray for highly-efficient oxygen evolution reaction - Yang, Qiu; Li, Tian; Lu, Zhiyi; Sun, Xiaoming; Liu, Junfeng (Nanoscale, 2014)
Efficient and low-cost electrocatalysts for the oxygen evolution reaction (OER) are essential components of renewable energy technologies, such as solar fuel synthesis and water splitting processes for powering fuel cells. Here, ultrathin NiCoFe layered double hydroxide (LDH) nanoplates, which directly grow on a cobalt-based nanowire array, forming a hierarchical nanoarray structure, are constructed as efficient oxygen evolution electrodes. In alkaline media, the ordered ultrathin hierarchical LDH nanoarray electrode shows dramatically increased catalytic activity compared to that of LDH nanoparticles and pure nanowire arrays due to the small size, large surface area, and high porosity of the NiCoFe LDH nanoarray. Only a small water oxidation overpotential (η) of 257 mV is needed for a current density of 80 mA cm(-2) with a Tafel slope of 53 mV per decade. The hierarchical LDH nanoarray also shows excellent structural stability in alkaline media. After continuous testing under a high OER current density (∼300 mA cm(-2)) for 10 h, the sample maintains the ordered hierarchical structure with no significant deactivation of the catalytic properties.